PARASITLSMO DE STREPTOCERYLE TORQUATA POR CATHAEMASIA RETICULATA WRIGHT 1879 HARWOOD 1936 TREMATODA ECHINOSTOMATIDAE - FLORES, LORENZO; CABALLERO Y C, EDUARDO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
Redescr of Crocodilicola pseudostoma parasitic on Crocodylus morellettii from the Cuetzalapan R, Veracruz, Mexico With this finding the dispersion area of the parasite enters the neotropical region
AN ESC NAC CIENC BIOL
Keywords: PARASITLSMO, STREPTOCERYLE TORQUATA, CATHAEMASIA RETICULATA, WRIGHT 1879 , HARWOOD 1936, TREMATODA: ECHINOSTOMATIDAE; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL